The Role of Absolute Pitch Memory in the Oral Transmission of Folksongs - Olthof, Merwin; Janssen, Berit; Honing, Henkjan (Empirical Musicology Review, 2015)
Absolute Pitch (AP) is the ability to identify or produce isolated tones in the absence of contextual cues or reference pitches. While AP is thought to differ from other human abilities in its bimodal distribution (Takeuchi & Hulse, 1993) – either you have it or you do not – recent evidence suggests that memory for absolute pitch in a melody is actually widespread (Schellenberg & Trehub, 2003). In the current project the Dutch collection of historic audio recordings, Onder de Groene Linde (Grijp, 2008), is used as a source to explore the potential role of AP in the memory of songs transmitted in oral traditions. Since the melodies in this database are grouped by tune family and are available as sound files, they can serve as empirical support for the Absolute Pitch Memory (APM) hypothesis predicting that these tunes are memorized and transmitted over time and geographical location based on their absolute pitch height. To this end, a between- and a within-tune family analysis was performed. In the between tune family analysis, two tune families showed significant inter-recording tonic pitch consistency. The within tune family analysis further substantialized that effect, while controlling for possible factors of variance, such as gender, geographical origin, and lyrics. Together, the results are taken as empirical support that APM plays a significant role in the oral transmission of folksongs.